Activation of Diazo Compounds by Fluorinated Triarylborane Catalysts - Pramanik, Milan; Melen, Rebecca L. (Synthesis, 2023)
The diverse applicability of diazo compounds as versatile reagents has enlarged the chemical toolbox in organic synthesis. Over the past few decades, transition-metal-catalyzed diazo compound activation has ignited the classical synthetic methodology via utilizing highly reactive metal carbenoid species. Many reviews have also appeared in the literature that show the advantages and disadvantages of metal-catalyzed activation of diazo compounds. Recently, tris(pentafluorophenyl)borane-mediated diazo activation reactions has remodeled this research area due to the potential for mild, environmentally friendly, metal-free, nontoxic reaction conditions, and the diverse reactivity patterns of boranes towards diazo compounds. In this review, we discuss the reactivity of the boron–diazo precursor adducts with compounds using catalytic and stoichiometric halogenated triarylboranes and, the mechanism of N2 release from the diazo reagent. This generates the reactive carbene species as a key intermediate which can further be exploited for O–H, N–H, S–H, and C–H insertions, azide insertion, carbonate transfer, C–C and C=C bond forming reactions, [2+2] or [2+4] cascade cyclization reactions, annulation reactions, etc.1 Introduction2 Diazo Activation Using Stoichiometric Boranes3 Diazo Activation Using Catalytic B(C6F5)34 B(C6F5)3-Catalyzed Diazo Activation Reactions5 Conclusions
Keywords: diazo activation; α-diazo ester; carbene formation; borane; catalysis